Distinguishing Characteristics of Urothelial Carcinoma in Kidney Transplant Recipients Between China and Western Countries - Liu, G.M.; Fang, Q.; Ma, H.S.; Sun, G.; Wang, X.C. (Transplantation proceedings, 2013)
To identify significant distinctive characteristics of urothelial carcinoma (UC) in kidney transplant recipients between China and Western countries and investigate probable tumor screening and treatment factors contributing to these differences. Renal transplant recipients from 1998 to 2011 in our institution diagnosed with UC were included in this study. Our data on tumor incidence, clinical characteristics, and outcomes were compared with literature reports. Among 2572 renal transplant recipients identified, 24 (0.93%) experienced UC, including 10 men and 14 women of overall mean age of 49.3 ± 11.6 years at transplantation and 53.5 ± 9.5 years at tumor detection. The Chinese traditional herbal intake mainly focused on 2 preparations: Aristolochic acid and rhubarb (the latter was mainly used in patients with chronic renal impairment) in 20 people. There were 21 (87.5%) cases of upper (UTUC) 5 cases of bilateral, and 13 cases of multifocal urinary tract urothelial carcinoma. Four subjects died owing to tumor progression at 4–63 months postoperatively. UC in renal transplant recipients shared notable characteristics in China with widespread herb intake: UTUC predominance; multifocal and bilateral organ involvement; high rates of recurrence, progression, and dissemination, in contrast with bladder tumor dominance in Western countries. As a consequence, we suggest that bilateral nephroureterectomy should be performed prophylactically in high-risk patients, especially those with a long history of Chinese herb intake. The relationship of rhubarb consumption to UC in renal transplant recipients should be noted and evaluated.